Caractérisation hydrodynamique des sols de la haute vallée de l'oued Sébaou (Algérie) : étude expérimentale, numérique et analytique - Ali Si Smail; Ali Bouheraoua; Malek Abdesselam (Physio-Géo)
Agricultural valley of High Sebaou is located in the region of Tizi-Ouzou in northern Algeria, it is Mediterranean climate. She has considerable reserves of groundwater in the form of an unconfined aquifer whose recharge and water quality are directly related to transfers of water and solutes from the soil surface. The study of these transfers requires, first, knowledge of hydrodynamic parameters of the unsaturated zone near the soil surface and the establishment of the characteristic curves K(h) et θ(h) reflecting the evolution of the hydraulic conductivity (K) and the water retention (θ) in terms of pressure heads (h). Measurements of infiltration, in situ, on five sites with different textures were made using a disc infilltrometer, using the multipotential method of ANKENY et al., by applying the suctions: -10, -6, -3, -1 and -0.5 cm successively. The measured cumulative infiltration [I(t)] associated with initial and final humidity has served as data in the numerical inversion with Hydrus-2D software to estimate the parameters of the MUALEM-VAN GENUCHTEN model (MVG) used in this study. In addition to the numerical inversion, curves K(h) and θ(h) were also established with the analytical methods (of WOODING and of ANKENY et al.) and from laboratory measurements on the sandbox. The effect of spatial variability of the initial moisture was examined by considering, for each test, the minimum, maximum and average measured values of the humidity. The results thus obtained show a perfect correlation between the measured and optimized cumulative infiltration with correlation coefficient very close to 1 (R2 > 0.993) and with variations intervals very small of the optimized parameters. The curves θ(h) obtained from the simulation and the laboratory are almost identical. However, as regards the curves K(h), a difference is found in the vicinities of saturation between the simulated and analytical methods. Besides, the spatial heterogeneity of the initial moisture has an impact on the optimized parameters of the MVG model, especially on hydraulic conductivity at saturation (Ks), which has very high coefficients of variation, with a maximum of the order of 60 %.